2017
DOI: 10.1002/ppsc.201700038
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydrogenation on Graphitic C3N4 Nanosheets for Enhanced Photocatalytic Activity

Abstract: Graphitic carbon nitride (g‐C3N4) has recently been studied as a promising metal‐free catalyst for photocatalytic hydrogen generation and environmental pollution removal. However, its photocatalytic activities are far from satisfactory, partially due to unsatisfied optical absorption and poor charge separation. Hydrogenation has recently been proven as an efficient approach in enhancing the optical absorption and improving the charge separation in oxide photocatalysts. In this study, the effects of hydrogenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 50 publications
(119 reference statements)
0
18
0
Order By: Relevance
“…However, the photocatalytic performance of bulk g-C 3 N 4 remains unsatisfactory because of the fast recombination rate of electron pairs and narrower light absorption range over the entire solar spectrum. Turning g-C 3 N 4 into a mesoporous nanorod structure [31] and the hydrogenation of g-C 3 N 4 [32] could be an alternative to increase the light-harvesting ability and charge separation efficiency. Our group has reported the self-modification of g-C 3 N 4 structures using alkaline [28] and acid treatment [29] to overcome the limitations of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the photocatalytic performance of bulk g-C 3 N 4 remains unsatisfactory because of the fast recombination rate of electron pairs and narrower light absorption range over the entire solar spectrum. Turning g-C 3 N 4 into a mesoporous nanorod structure [31] and the hydrogenation of g-C 3 N 4 [32] could be an alternative to increase the light-harvesting ability and charge separation efficiency. Our group has reported the self-modification of g-C 3 N 4 structures using alkaline [28] and acid treatment [29] to overcome the limitations of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that there is almost no H 2 was produced on bare g‐C 3 N 4 . The hydrogen production rate of g‐C 3 N 4 was improved by preparing g‐C 3 N 4 with various structures and morphologies, doping metal and nonmetallic atoms, loading cocatalysts, etc. The supported cocatalyst can effectively reduce the recombination of photogenerated carriers and improve the hydrogen production activity of g‐C 3 N 4 due to reduction of Schottky barrier …”
Section: Introductionmentioning
confidence: 99%
“…[29] Meng et al found that the surface oxygen vacancy overlayer of TiO 2 can be formed via hydrogenation with Pt loading, and the surface defects are responsible for its high catalytic activity due to the suppression of electron-hole recombination. [30] Similarly, introducing oxygen vacancies or deficient by hydrogenation can enhance photocatalytic activities of TiO 2 [31] ZnO, [32] CeO 2 , [33] BiOCl, [34] g-C 3 N 4 [35] and BiPO 4 . [36] The crystal structure of SrTiO 3 is very stable because of high oxygen binding energy.…”
Section: Introductionmentioning
confidence: 99%